The Nordic Journal of Aesthetics No. 47 (2014), pp. 125–142 Commodification and Subjectivization - Toward a Critique of the Authorship Discourse - Johansson, Anders (The Nordic Journal of Aesthetics, 2016)
What does it mean that the author increasingly turns into a commodity? The article contains a discussion of some academic responses – taken from celebrity studies and autofiction studies – to this tendency. The texts discussed share an effort to rethink authorship, but nonetheless the implicit result is a reinforcement of a traditional, romantic notion of the author. Above all there is a lack of reflection on subjectivity in the authorship discourse, where concepts like “author”, “subject”, “self” often are treated as synonymous. In that sense the academic responses are part of the commodification they ought to be studying. On another level this commodification could be understood as an expression of a more general crisis of subjectivity: there is a need of stories about autonomous subjects just because of a more extensive desubjectivation. Finally the article turns to Theodor W. Adorno and Jacques Rancière in order to find a more dynamic and apt understanding of subjectivity.